CURRENT ISSUES IN MATHEMATICS TEACHING METHODOLOGY - Gafurova Mavjuda Aliyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Mathematics education is one of the most important factors determining the level of economic and socio-political development of a country. The article examines current problems in teaching mathematics and provides recommendations for solving them. A brief summary of the essence of pedagogical technologies and their role in the process of teaching mathematics is given. The fundamental difference between a modern lesson and a traditional one, as well as the requirements of mathematics teachers, are given. The methodology of teaching mathematics in universities is analyzed.